Empowerment in Geographical Environmental Education at School - Heimel, Hauke Jan; Otto, Karl-Heinz (Journal of Geography Education, 2006)
There are two main ideas referring to empowerment: As a cultural term empowerment means a synthetic system of values which connects human egoism and altruism. As a strategic term empowerment means a strategy of becoming stronger by oneself or of making someone stronger in order to change structures of political power or at least conditions of individual and social life. This literature-based definition is the key to a general educational empowerment concept with two partial strategies: orientation towards facts as well as towards strengths. The environmental educational empowerment concept is focused on challenging and training human potentials and on protecting and developing environmental potentials. A descriptive-statistical survey with 1,295 usable questionnaires led to a lot of results that make an implementation of empowerment especially in geography lessons not only possible but also necessary. After all geography is a subject that creates a bridge between human and physical geography, between man and environment. In combination with general techniques of evaluating human potentials (pupils’ competencies), certain environmental empowerment modules allow pupils an active, critical and competent analysis of selected examples and especially of their environmental potentials.